Analisis Yuridis Tindak Pidana Perpajakan sebagai Salah Satu Modus Operandi Tindak Pidana Korupsi di Indonesia - Aldi Wildan Maris (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This study examines the relationship between tax crimes and corruption in Indonesia from a legal standpoint, employing a qualitative methodology, case study method, and document analysis. Secondary data were gathered from journals, legislation and regulations, and official publications and examined using qualitative content analysis methods. The findings indicate that tax crimes, such as data manipulation and the production of bogus invoices, are frequently utilized to conceal assets originating from corruption. Bribery is a common form of tax corruption. To summarize, tightening legislation, expanding the capacity of law enforcement officials, international collaboration, changing the tax system, and raising taxpayer awareness are required to reduce tax crime and corruption and strengthen the country's economy.